HALP score in Demodex blepharitis: A case–control study - Cakir Nuri; Pangal Emine; Cakir Isil; Yaman Ozan; Bayram Nurettin (Open Medicine)
Demodex mite infestation is one of the most prevalent causes of blepharitis. This study was designed to evaluate whether Demodex blepharitis was related to novel inflammatory markers.